Genotyping of Candida albicans Isolated from broilers by 25S rDNA Analysis - Hiader Tuma Kaab (Kufa Journal for Veterinary Medical Sciences, 2013)
Candida albicans one of the most fungi which isolated from clinical samples that cause many problems to humans, animals and birds. Candidiasis is an opportunistic endogenous mycosis in that perturbance of the microflora or other debilitation of the host.  So, this study come to focused on genotyping and antifungal susceptibility profile to Candida albicans isolated from broilers.